Redesign Meja Belajar yang Ergonomis untuk Siswa Disabilitas Menggunakan Metode Pahl And Beitz dan Value Engineering di Yayasan Pembinaan Anak Cacat (YAPC) Surabaya - Prasanto, Fadhil Aditya; Tranggono, Tranggono; Rachmawati, Nur (Ekonomis: Journal of Economics and Business, 2025)
This study aims to redesign ergonomic study table products for physically disabled students using the Pahl and Beitz method and Value Engineering at the 'Yayasan Pembinaan Anak Cacat (YAPC)' Surabaya. The results obtained from the Pahl and Beitz method are ergonomic multifunctional study table products with specifications of 81 cm long and 54 cm wide with table legs that can be adjusted from 65-70 cm so that users feel comfortable when using the study table. With the value engineering method, the addition of new features to the study table obtained an increase in value from 1.00 to 2.18 with a minimum price of Rp 920,000. The value engineering method helps in identifying raw materials for making tables and more efficient and economical technology when making this multifunctional study table. Thus, the production cost of this study table can be reduced, but the safety factor for using the table is still guaranteed.